THE IMMUNE SYSTEM IN CHILDREN WITH VARIOUS FROMS OF EARLY CONGENITAL SYPHILIS - G. P. Martynova; N. F. Kuznetsova (LLC "Diagnostics and Vaccines", 2017)
The results of immunological monitoring of 40 children with early congenital syphilis in the acute period and after specific therapy. Revealed that the severity of changes in the immune system depend on the clinical form of the disease and the most significant group of children with polisimptomnym over syphilitic infection. The majority of the investigated immunological parameters after specific therapy in patients of this group are not restored to control values, which can be regarded as serious, not smooth during desease. Babies with early monosemeiotic form of congenital syphilis immunological indicators partially recovered, indicating a possible protracted course of the process. At the same time, patients with latent form of the disease immunological parameters restored to control values, which suggest a favorable prognosis.